2015
DOI: 10.3855/jidc.5149
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of P1 and 16S rRNA genes for detection of Mycoplasma pneumoniae by nested PCR in adults in Zhejiang, China

Abstract: Introduction: Mycoplasma pneumoniae (M. pneumoniae) is the most common atypical pathogen that causes respiratory infections in humans. Laboratory tests are important in the diagnosis of M. pneumoniae because of the atypical features in clinical signs and symptoms. Nowadays, both the P1 adhesin gene and 16S ribosomal (r) RNA (rRNA) gene of M. pneumoniae have been widely detected by polymerase chain reaction (PCR). The purpose of the present study was to evaluate the most suitable target in the detection of M. p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…pneumoniae and its gene is an attractive target in the clinical detection of M . pneumoniae by real-time PCR 10 17 . This is the first study detecting P1 antigen to confirm M. pneumoniae infection in children with pneumonia.…”
Section: Discussionmentioning
confidence: 99%
“…pneumoniae and its gene is an attractive target in the clinical detection of M . pneumoniae by real-time PCR 10 17 . This is the first study detecting P1 antigen to confirm M. pneumoniae infection in children with pneumonia.…”
Section: Discussionmentioning
confidence: 99%
“…Other gene targets have included 16S rRNA, the 16S-23S rRNA spacer, the CARDS toxin gene, the ATPase operon, dnaK, pdhA, tuf, parE, pdhA, ptsL, and the noncoding repetitive element in repMp1. Assays targeting the P1 gene have been reported to be more sensitive than those targeted at the 16S rRNA by Ieven et al (302), but the reverse result was found in a comparative study by Zhou et al (303). A study by Peters et al (217) showed that the CARDS toxin PCR detected M. pneumoniae in 10-fold more patients than a PCR using the P1 protein gene as the gene target.…”
Section: Nucleic Acid Amplificationmentioning
confidence: 99%
“…In this study, the analytical sensitivity of the assay for M. pneumoniae was 2.23 copies (19.4 fg) per reaction, while the sensitivity of the commercial real-time PCR assay used here for comparison is only 500 copies per reaction according to the manufacturer, suggesting that the RAA assay is more sensitive. Our RAA assay also achieved the same level of sensitivity reported for realtime PCR methods, which ranges from 0.83 fg-100 fg per reaction [21][22][23][24].…”
Section: Discussionmentioning
confidence: 56%
“…Sequence variation within the target region can affect the detection results of molecular diagnostic methods. Previously reported targets for M. pneumoniae include 16S rRNA, P1, RepMP1, and the CARDS toxin [21][22][23][24]. Among these, the P1 gene has offered high specificity and diagnostic efficiency.…”
Section: Discussionmentioning
confidence: 99%